Two-step inertial forward-reflected-backward splitting based algorithm for nonconvex mixed variational inequalities - Izuchukwu, Chinedu; Shehu, Yekini; Dong, Qiao-Li (Journal of computational and applied mathematics, 2023)
This paper presents a modification of a recently studied Malitsky–Tam forward-reflected-backward splitting method with two-step inertial extrapolation to solve nonconvex mixed variational inequalities. We give global convergence results and nonasymptotic O(1/k) convergence rate of our proposed method under some appropriate conditions and present some mathematical justifications.